Modelling the two-phase performance of a centrifugal pump - Downham, S. E. (Cranfield University, 2000)
A review was carried out which revealed that no simple mathematical model was available which could be used to predict the performance of a centrifugal pump when it is operating under two phase flow conditions. Experimental analyses were carried out to aid the development of such a model. A rotating channel test rig was designed to study the structure of airwater flow through an impeller passageway. The observations generated a large amount of qualitative data. A full scale centrifugal pump was also tested which provided data that allowed the results of the rotating channel experiments to be considered in more quantitative terms. These two sets of experimental work allowed a conceptual model of the two phase flow through a centrifugal pump to be constructed. The model assumes that forces act on the bubbles as they pass through the impeller passageway because of the rotation and the curvature of the impeller passageway. These forces cause the bubbles to decelerate and coalesce creating a stationary air void which leads to a partial blockage of the channel. This causes the velocity of the fluid passing through the pump to be modified. The model uses a onedimensional velocity vector approach adjusted for hydraulic losses to calculate the head raised by the pump under such conditions. The model presented provides the basis upon which a predictive tool could be developed and used in the development engineering environment. Currently operational problems that arise because of two phase flow are often quantified using scaled hydraulic models, which are expensive, or within the actual application where costly engineering solutions may be required to give acceptable performance. A mathematical model is a much more cost effective tool and its application allows the engineer to decide whether system performance would be compromised by the two phase conditions encountered and propose possible solutions. In recommending the development of such a model it is necessary to consider where and how in the project cycle it should be used. A number of companies were canvassed and it was concluded that in many cases such models are used too late in the project cycle to provide maximum return. In the case of projects which include participants from a number of companies it is suggested that an inter-company team should be constructed if development models are to be widely used. This team should be used to plan and implement the use of development models efficiently and ensure that the data produced is communicated effectively and is of the maximum value to the participants.